POSITIONING FIT AND CATEGORY FIT DURING BRAND - SLADE, DOMINIC JOHNATHAN (My University, 2011)
Brand extensions are a popular method adopted by marketers and brand custodians to enhance and augment brand equity and there have been numerous studies undertaken to determine the factors that play a role during this brand-building process. Most of these have highlighted the importance of category fit. The purpose of this Research Report has been to examine both category fit and positioning fit during brand extensions and determine the relative importance of positioning fit. The Delphi Technique was selected as the methodology for this piece of research. The panel selected included a broad range of marketers, strategists and consultants including Rae McGraw (Marketing Director, Dulux), Derek Carstens (Brand Director, FirstRand), Siyabonga Khuzwao (Brand Manager, Unilever), Mike Perry (Founder, Perry & Associates) and Sarah Mathems (Managing Director, Original Insight Learning). The initial findings of this research indicate that current marketer thinking does not assign a critical role to positioning fit during the process of brand extensions. However, later stages of the research and subsequent analysis indicate that positioning fit certainly plays a role and should be one of the factors considered when undertaking brand extensions.
MBA - WBS
Keywords: Brands and branding